Pelatihan Penyusunan Perangkat Asesmen Keterampilan Menulis Deskripsi - Angla Florensy Sauhenda; Marnina Marnina; Margaretha F Narahawarin (Lembaga Pengembangan Kinerja Dosen, 2024)
This community service activity aims to improve the ability of Indonesian language teachers in compiling assessment tools for descriptive writing skills. This community service activity was carried out at Gudang Arang Merauke State Middle School with 6 Indonesian language teachers participating. With this service activity, teachers can understand how to prepare assessment tools for descriptive writing skills in the form of teacher guidelines and student assignments. This service contributes to Indonesian language subjects. This service is carried out in the form of a workshop which includes socialization in the form of training and mentoring and ends with a joint discussion.